(untitled) (Journal of Psychiatrists’ Association of Nepal, 2019)
Psychosis is a mental disorder in which the thoughts, affective response, ability to recognise reality and ability to communicate and relate to others are significantly impaired to interfere grossly with the capacity to deal with the reality. Psychosis can also occur as a side effect of some type of drugs and may be misdiagnosed as psychiatric illness. We report a rare case of 30 years old female admitted to Nepal Medical College with hallucinations and delusions following ofloxacin use, by extensive / detailed history taking.